Teacher's Personality Competence in Improving Student Learning Manners - Kusworo, Singgih; Zulham, Zulham (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the personality competence of Islamic Religious Education teachers in improving student learning manners at MAPN 4 Medan Martubung. The data form of this research consists of primary and secondary data. Primary data was obtained through interviews with two Islamic Religious Education teachers, one other subject teacher, and three students, as well as direct observation and documentation related to the learning process. Secondary data includes relevant documents and photos from the school. All of this data was analyzed using qualitative methods using the Miles and Huberman interactive model, which includes collecting, reducing, presenting data, and drawing conclusions to understand the teacher's personality competence on student learning manners. The results showed that teachers' personality competencies, which include discipline, wisdom, wisdom, and noble character, play an important role in shaping students' learning manners. Teachers are not only role models in attitude and behavior but also active in guiding students to instill adab values in everyday life. Habituation of manners such as sincere intention in studying, praying before and after learning, and speaking politely are the main focus in improving students' learning manners. In addition, supporting factors such as a conducive school environment also play a role in the development of student manners, while differences in students' ability to receive material are one of the inhibiting factors. Overall, teachers' personality competence has a big influence on the quality of learning and students' manners, so it is important for teachers to continue to develop themselves and create a learning environment that supports students' character development.